Intronic Variant in CNTNAP2 Gene in a Boy With Remarkable Conduct Disorder, Minor Facial Features, Mild Intellectual Disability, and Seizures - Falsaperla, Raffaele; Pappalardo, Xena Giada; Romano, Catia; Marino, Simona Domenica; Corsello, Giovanni; Ruggieri, Martino; Parano, Enrico; Pavone, Piero (Frontiers in Pediatrics, 2020)
Introduction: Mutations in the contactin-associated protein-like 2 (CNTNAP2) gene (MIM#604569) encoding for CASPR2, a cell adhesion protein of the neurexin family, are known to be associated in autism, intellectual disability, and other neuropsychiatric disorders. A set of intronic deletions of CNTNAP2 gene has also been suggested to have a causative role in individuals with a wide phenotypic spectrum, including Pitt-Hopkins syndrome, Cortical Dysplasia-Focal-Epilepsy Syndrome, Tourette syndrome, language dysfunction and abnormal behavioral manifestations. Case presentation: A 10-year-old boy was referred to the hospital with mild intellectual disability and language impairment. Moreover, the child exhibited minor facial features, epileptic seizures, and notable behavioral abnormalities including impulsivity, aggressivity and hyperactivity suggestive of the diagnosis of disruptive, impulse-control and conduct disorder (CD). Array CGH revealed a CNV deletion in the first intron of CNTNAP2 gene inherited from healthy father. Conclusions: A comprehensive description of the phenotypic features of the child is provided revealing a distinct and remarkable alteration of social behavior not previously reported in individuals affected by disorders related to CNTNAP2 gene disruptions. A possible causative link between the deletion of a non-coding regulatory region and the symptoms presented by the boy has been advanced.